Prevalence of suicide ideation, self-harm, and suicide among Chinese patients with schizophrenia: a systematic review and meta-analysis - Liang, Yiying; Wu, Manqi; Zou, Yanqiu; Wan, Xiaoyan; Liu, Yuanyuan; Liu, Xiang (Frontiers in Public Health, 2023)
Aims. Suicide ideation, self-harm, and suicide are common in patients with schizophrenia, but the results vary largely across different studies. Improved prevalence estimates and identification of moderators of the above self-directed violence are needed to enhance recognition and care, and to guide future management and research. This systematic review aims to estimate the pooled prevalence and identify moderators of suicide ideation, self-harm, and suicide among patients diagnosed with schizophrenia in China . Methods. Relevant articles published until September 23, 2021, were searched using PubMed, EBSCO, Web of Science, Embase, Science Direct, CNKI, CBM, VIP, and Wanfang databases. Eligible studies published in English or Chinese which reported the prevalence of suicide ideation, self-harm, or suicide among Chinese patients with schizophrenia were collected. All studies passed a quality evaluation. This systematic review was registered with PROSPERO (registration number CRD42020222338). PRISMA guidelines were used in extracting and reporting data. Random-effects meta-analyses were generated using the meta package in R. Results. A total of 40 studies were identified, 20 of which were evaluated as high-quality studies. Based on these studies, the prevalence of lifetime suicide ideation was 19.22% (95% CI: 7.57%-34.50%), prevalence of suicide ideation at the time of investigation was 18.06% (95% CI: 6.49%-33.67%), prevalence of lifetime self-harm was 15.77% (95% CI: 12.51%-19.33%), and prevalence of suicide was 1.49% (95% CI: 0.00%-7.95%). Multivariate meta-regression analysis revealed that age (β=−0.1517, P=0.0006) and dependency ratio (β=0.0113, P<0.0001) were associated with the lifetime prevalence of self-harm. Study assessment score (β=0.2668, P<0.0001) and dependency ratio (β=0.0050, P=0.0145) were associated with the lifetime prevalence of suicide ideation. Results of the spatial analysis showed that the prevalence of self-directed violence varied greatly across different provinces. Conclusions. This systematic review provides estimates of the prevalence of self-directed violence among Chinese patients with schizophrenia and explores its moderators and spatial patterns. Findings also have important implications for allocating prevention and intervention resources to targeted high-risk populations in high prevalence areas.